Topoisomerase I inhibitor, camptothecin, induces apoptogenic signaling in human embryonic stem cells - Garcia, Carolina Paola (2013)
Embryonic stem cells (ESCs) need to maintain their genomic integrity in response to DNA damage to safeguard the integrity of the organism. DNA double strand breaks (DSBs) are one of the most lethal forms of DNA damage and, if not repaired correctly, they can lead to cell death, genomic instability and cancer. How human ESCs (hESCs) maintain genomic integrity in response to agents that cause DSBs is relatively unclear. In the present study we aim to determine the hESC response to the DSB inducing agent camptothecin (CPT). We find that hESCs are hypersensitive to CPT, as evidenced by high levels of apoptosis. CPT treatment leads to DNA-damage sensor kinase (ATM and DNA-PKcs) phosphorylation on serine 1981 and serine 2056, respectively. Activation of ATM and DNA-PKcs was followed by histone H2AX phosphorylation on Ser 139, a sensitive reporter of DNA damage. Nuclear accumulation and ATM-dependent phosphorylation of p53 on serine 15 were also observed. Remarkably, hESC viability was further decreased when ATM or DNA-PKcs kinase activity was impaired by the use of specific inhibitors. The hypersensitivity to CPT treatment was markedly reduced by blocking p53 translocation to mitochondria with pifithrin-μ. Importantly, programmed cell death was achieved in the absence of the cyclin dependent kinase inhibitor, p21Waf1, a bona fide p53 target gene. Conversely, differentiated hESCs were no longer highly sensitive to CPT. This attenuated apoptotic response was accompanied by changes in cell cycle profile and by the presence of p21Waf1. The results presented here suggest that p53 has a key involvement in preventing the propagation of damaged hESCs when genome is threatened. As a whole, our findings support the concept that the phenomenon of apoptosis is a prominent player in normal embryonic development.